Monitoriella Hedqvist (Hymenoptera: Braconidae: Doryctinae) from Brazil, with descriptions of three new species - Shimbori, Eduardo Mitio; Penteado-Dias, Angélica Maria; Nunes, Juliano Fiorelini (Zootaxa, 2011)
Monitoriella Hedqvist is a phytophagous, gall-inducer Braconidae genus, known only from the New World. Its placement in a higher taxonomic level has been uncertain until recent phylogenetic investigations on cyclostome braconids, which reinforce its position in Doryctinae. Three new species of Monitoriella are described: M. costalimai sp. nov., M. spinata sp. nov., and M. ubatuba sp. nov., all from the Brazilian Atlantic Forest. Monitoriella anthurii is redescribed and illustrated. A key to all known species is provided.